إسهامات الرياضة المدرسية في إنتقاء المواهب الرياضية في مرحلة التعليم المتوسط - العربي, سفيان (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
تهدف الدراسة إلى معرفة مدى إسهامات الرياضة المدرسية في انتقاء وصقل المواهب الرياضية في مرحلة التعليم المتوسط من وجهة نظر الأساتذة. ولأجل ذلك اتبعنا المنهج الوصفي بالأسلوب المسحي بالإعتماد على استبيان موجه لأساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسط، حيث ضمت (34) أستاذ من بعض متوسطات ولاية معسكر. وجاءت أهم نتائج البحث إلى أن الرياضة المدرسية تسهم بشكل إيجابي في انتقاء وصقل المواهب الرياضية في مرحلة التعليم المتوسط من وجهة نظر الأساتذة، حيث أكد الأساتذة أن الأنشطة الرياضية المدرسية توفر بيئة مناسبة انتقاء وصقل المواهب الرياضية // // // // Research title: ‘The contributions of school sports in selecting sports talents at the intermediate education stage’ This study aims to find out the extent of the contributions of school sports in the selection and refinement of sports talents at the intermediate education level from the point of view of teachers. For this purpose, we followed the descriptive survey method based on a questionnaire addressed to the teachers of physical education and sports at the intermediate education level, which included (34) teachers from the averages of the state of Camp. The main findings of the research indicated that school sports contribute positively to the selection and refinement of sports talents at the intermediate education level from the perspective of the teachers, as the teachers emphasised that school sports activities provide a suitable environment for the discovery of talented students.
MEPS-2025-2
Keywords: School sport - Selection and refinement - Sports talents // // // الرياضة المدرسية - الإنتقاء - المواهب الرياضية